Factors Affecting Rupture Perineum on Mother Maternity at District Health Clinics Kramat Jati, East Jakarta in Januari to May 2013: Royani Chairiyah, Warsiningsih - Chairiyah, Royani; Warsiningsih, Warsiningsih (Jurnal Persada Husada Indonesia, 2015)
Rips the birth canal is the second leading cause after an atonic and often occurs in primiparous due to the time of delivery do not get a strong grip, causing a tear in the perineum (South Bone, 2012). The data District Health Clinics Kramat Jati, East Jakarta, normal delivery in 2011 as many as 559 people found the case of rupture of the perineum as many as 430 people (60%), while in 2012 as many as 538 people a normal delivery with perineal rupture as much as 373 people (69%). The incidence of rupture of the perineum in PHC Kramat Jati, East Jakarta increasing the period of January to May 2013, 179 people with the amount of maternity perineal rupture 138 people (77%), rupture of the perineum grade I-II 87% and grade III-IV 13%. The purpose of this study to determine the factors that affect the incidence of maternal perineal rupture in Kramat Jati Jakarta District Health Clinics east period from January to May 2013. This study uses an analytical method premises number of respondents 138 people. The results of the research that the frequency distribution of rupture of the perineum by 138 people (77%), there was no significant association between maternal age on the incidence of rupture of the perineum, the value of P value is 0.692 or ≥ 0.05, there is a significant relationship between the baby's weight on the incidence of rupture of the perineum , with the value of the P value is 0.000 or ≤ 0.05, there is a significant relationship between the parity of the incidence of rupture of the perineum, the value of the P value is 0.033 or ≤ 0.05. From the results of research based on three variables in this study is the variable weight infants 2500-4000 grams of the rupture of the perineum Grade I-II as many as 118 infants (93.7%). Suggestions for health centers are expected to increase efforts to prevent rupture of the perineum by providing counseling on maternal how meneran right to prevent rupture of the perineum and motivate pregnant women to pregnancy exercise and massage the perineum to reduce the incidence of rupture of the perineum.